Unveiling the Challenges and Opportunities Behind Social Determinants of Health (SDOH): Data Security, Clinical Coding, and EMR Standards in Indonesia's Digital Health Era - Widiyanto, Wahyu Wijaya; Licia, Rizka; Sukmaningsih , Wahyu Ratri (Procedia of Engineering and Life Science, 2024)
The increasing adoption of Electronic Medical Records (EMR) in Indonesia has brought about significant challenges related to data security, consistency in clinical coding, and the influence of Social Determinants of Health (SDOH). These issues are critical as they impact the effectiveness and reliability of healthcare information systems, potentially compromising patient data and the quality of healthcare services. This study employed a systematic review of 25 relevant articles published between 2018 and 2023. The articles were analyzed using the PRISMA approach to identify gaps in the literature concerning the implementation of EMR, data security, and clinical coding standards in Indonesia. The review also explored the role of SDOH in influencing these factors. The objective of this study was to explore the challenges and opportunities in integrating SDOH with data security and clinical coding within the framework of EMR implementation, with a specific focus on Indonesia’s healthcare sector. The findings indicate that data security remains a critical issue, with many healthcare institutions in Indonesia not fully implementing adequate security measures. The study also revealed inconsistencies in clinical coding standards across institutions, with only 60% adopting internationally recognized coding systems. Additionally, SDOH such as digital literacy and access to technology significantly affect EMR adoption, with regions having better technological access showing more effective implementation.